Biocharcoal dari Serbuk Gergaji Kayu Cempaka (Elmerrillia ovalis Miq) serta Daya Adsorpsinya pada Zink dan Tembaga - Susilawati, Niluh Eka; Walanda, Daud K.; Napitupulu, Mery (Universitas Tadulako, 2015)
Cempaka wood is a typical wood in Sulawesi Island and Maluku archipelago. This wood can be used for wood industry particularly for the manufacture of furniture. However, not only furniture can be produced from the wood but also the sawdust as the waste. This research utilized the sawdust of cempaka wood as biocharcoal to adsorb zinc and copper ions included in liquid organic fertilizer complement based on variation of weight and concentration of biocharcoal. The method used in this study was the spectrophotometry spectroDirect with sawdust of cempaka wood as the adsorbent. The results showed the characteristic of water content of biocharcoal was 4.05% while ash content was 7.75%. The optimum weight of biocharcoal to adsorb zinc ions was 40 mg with the adsorption capacity of 19.97 mg/g while for copper ions was 60 mg with the adsorption capacity of 16.16 mg/g. The optimum concentration of zinc and copper ions than can be adsorbed was 60 ppm with the adsorption capacity of 11.80 mg/g for copper ion and 9.29 mg/g for zinc ion.